Strategies of representation in auto/biography reconstructing and remembering - Hove, Muchativugwa; Masemola, Kgomotso; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
This book investigates how selves are represented and reconstructed in selected auto/biographies in African literary discourse and examines how this relates to issues of identity, nation and history.
Keywords: Linguistics; Ethnology -- Africa; Literature; Sociolinguistics; Linguistics; Sociolinguistics; Literature, general; African Culture